Media's effect on athletes' mental health - Ng, T.; Sanders, H.; Merrill, S.; Faustin, M. (Clinics in Sports Medicine, 2024)
This article explores the athlete's relationship with both traditional and social (digital) media and describes athletes' media obligations and the pressures of media attention. It explains the difference in the representation of diverse groups, and the potential positive and negative outcomes of the media on an athlete's mental health. The article will review the emergence of social media, its limitless reach, and ways in which it diverges from traditional media coverage of athletic performance. Finally, the article concludes with a discussion of ways that athletes' multidsciplinary medical teams may become advocates for healthy and supportive interactions between athletes and media.